Promising Shadow Masking Technique for the Deposition of High-Efficiency Amorphous Silicon Solar Cells Using Plasma-Enhanced Chemical Vapor Deposition - Alaoui, Kawtar Belrhiti; Laalioui, Saida; Ikken, Badr; Outzourhit, Abdelkader (Frontiers in Mechanical Engineering, 2020)
In this work, a detailed description of the various steps involved in the fabrication of high-efficiency hydrogenated amorphous-silicon cells using plasma-enhanced chemical vapor deposition, and a novel shadow masking technique is presented. The influence of the different masking methods on the cell parameters was experimentally investigated. Particularly, the short-circuit current density (Jsc), the fill factor, the open circuit voltage (Voc), and the resistive losses indicated by the shunt (Rsh) and series (Rs) resistances were measured in order to assess the performance of the cells as a function of the masks used during the cell fabrication process. The results indicate that the use of a masking technique where the p-i-n structure was first deposited over the whole surface of a 20 cm2 × 20 cm2 substrate, followed by the deposition, deposits the back contact through a metal mask, and by the ultrasonic soldering of indium to access the front contact is a good alternative to laser scribing in the laboratory scale. Indeed, a record efficiency of 8.8%, with a short-circuit current density (Jsc) of 15.6 mA/cm2, an open-circuit voltage (Voc) of 0.8 V, and a fill factor of 66.07% and low resistive losses were obtained by this technique. Furthermore, a spectroscopic ellipsometry investigation of the uniformity of the film properties (thickness, band gap, and refractive index) on large-area substrates, which is crucial to mini-module fabrication on a single substrate and for heterojunction development, was performed using the optimal cell deposition recipes. It was found that the relative variations of the band gap, thickness, and refractive index n are less than 1% suggesting that the samples are uniform over the 20 cm2 × 20 cm2 substrate area used in this work.